2020
DOI: 10.1007/s00280-020-04173-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma deoxyuridine as a surrogate marker for toxicity and early clinical response in patients with metastatic colorectal cancer after 5-FU-based therapy in combination with arfolitixorin

Abstract: Purpose The aim was to explore the correlation between increasing doses of [6R]-5,10-methylenetetrahydrofolate (arfolitixorin) and plasma concentrations of deoxyuridine (dUr) in patients with metastatic colorectal cancer (mCRC), subjected to 5-fluorouracil (5-FU)-based chemotherapy. The aim was further to investigate the possibility to predict toxicity and clinical response during treatment using gender, age, and plasma dUr as explanatory variables. Methods Thirty-three patients from the ISO-CC-005 phase I/I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Plasma concentrations of the biologically active molecule ([6R]-MTHF) and its metabolites (THF and methyl-THF) increased linearly with the dose increase of arfolitixorin from 30 to 240 mg/m 2 , indicating that higher plasma levels are reached with higher doses. On the basis of existing evidence associating folate plasma concentrations with early treatment response, 27 a higher dose of arfolitixorin may elicit a greater treatment response than lower doses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma concentrations of the biologically active molecule ([6R]-MTHF) and its metabolites (THF and methyl-THF) increased linearly with the dose increase of arfolitixorin from 30 to 240 mg/m 2 , indicating that higher plasma levels are reached with higher doses. On the basis of existing evidence associating folate plasma concentrations with early treatment response, 27 a higher dose of arfolitixorin may elicit a greater treatment response than lower doses.…”
Section: Discussionmentioning
confidence: 99%
“…This decision was also supported by a published subset analysis of 33 patients, who were initially enrolled into the PK analysis set of this trial. 27 The analysis found that levels of plasma deoxyuridine, a surrogate marker for toxicity and early clinical response, were significantly higher 24 h into cycle 1 with arfolitixorin 120 mg/m 2 than with 30 or 60 mg/m 2 . 27 This suggests that arfolitixorin 120 mg/m 2 elicits an earlier clinical response than with the lower doses of 30 and 60 mg/m 2 , and the findings of this study indicate that this dose has a manageable safety and tolerability profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subanalysis of that study also indicated that plasma deoxyuridine (a surrogate marker of cytotoxicity and early clinical response) was significantly higher with increasing dose of arfolitixorin ( P = 0.023; ref. 23 ). Consequently, this was the dose evaluated in this phase III study.…”
Section: Discussionmentioning
confidence: 99%
“…5-Fluorouracil (5-FU) is an anti-metabolic antitumor drug, which can inhibit thymine nucleotide synthetase and interfere with DNA synthesis ( Taflin et al, 2021 ). It exerts significant antitumor effect in a variety of tumors ( Akalovich et al, 2021 , Proietti et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%